Helicoidal Organization of Chitin in the Cuticle of the Migratory Locust Requires the Function of the Chitin Deacetylase2 Enzyme (LmCDA2) - Yu, R. R.; Liu, W. M.; Li, D. Q.; Zhao, X. M.; Ding, G. W.; Zhang, M.; Ma, E.; Zhu, Kun Y.; Li, S.; Moussian, B.; Zhang, J. Z. (My University, 2016)
In the three-dimensional extracellular matrix of the insect cuticle, horizontally aligned microfibrils composed of the polysaccharide chitin and associated proteins are stacked either parallel to each other or helicoidally. The underlying molecular mechanisms that implement differential chitin organization are largely unknown. To learn more about cuticle organization, we sought to study the role of chitin deacetylases (CDA) in this process. In the body cuticle of nymphs of the migratory locust Locusta migratoria, helicoidal chitin organization is changed to an organization with unidirectional microfibril orientation when LmCDA2 expression is knocked down by RNA interference. In addition, the buCDA2-deficient cuticle is less compact suggesting that LmCDA2 is needed for chitin packaging. Animals with reduced LmCDA2 activity die at molting, underlining that correct chitin organization is essential for survival. Interestingly, we find that LmCDA2 localizes only to the initially produced chitin microfibrils that constitute the apical site of the chitin stack. Based on our data, we hypothesize that LmCDA2-mediated chitin deacetylation at the beginning of chitin production is a decisive reaction that triggers helicoidal arrangement of subsequently assembled chitin-protein microfibrils.
Citation: Yu, R. R., Liu, W. M., Li, D. Q., Zhao, X. M., Ding, G. W., Zhang, M., . . . Zhang, J. Z. (2016). Helicoidal Organization of Chitin in the Cuticle of the Migratory Locust Requires the Function of the Chitin Deacetylase2 Enzyme (LmCDA2). Journal of Biological Chemistry, 291(47), 24352-+. doi:10.1074/jbc.M116.720581
Keywords: Peritrophic Matrix; Drosophila-Melanogaster; Tribolium-Castaneum; Proteins; Expression; Membrane